2018
DOI: 10.1097/md.0000000000012931
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between controlled attenuation parameter and metabolic syndrome and its components in middle-aged and elderly nonalcoholic fatty liver disease patients

Abstract: This study aims to investigate the correlation between controlled attenuation parameter (CAP) and metabolic syndrome (MetS) and its components in middle-aged and elderly nonalcoholic fatty liver disease (NAFLD) patients.Middle-aged and elderly patients with NAFLD, who visited our hospital from June 2016 to May 2017, were enrolled as study subjects, whereas middle-aged and elderly patients without liver disease were enrolled as controls in the same period. The prevalence of MetS, MetS components, and the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
2
13
0
2
Order By: Relevance
“…The new models of FibroScan (marketed after 2013) can assess the staging of NAFLD using a liver stiffness score (E score) and a liver steatosis score (controlled attenuation parameter [CAP] score). Interestingly, the CAP score alone was found to be a useful indicator of the presence and severity of metabolic syndrome [18]. Using traditional statistical modeling, we previously validated this finding, confirming that the CAP score alone can be used to detect metabolic syndrome with moderate accuracy (area under the receiver operating characteristic curve [ROC] of 0.79), and the accuracy was improved to 0.88 when combined with other biomarkers [19].…”
Section: Introductionmentioning
confidence: 61%
“…The new models of FibroScan (marketed after 2013) can assess the staging of NAFLD using a liver stiffness score (E score) and a liver steatosis score (controlled attenuation parameter [CAP] score). Interestingly, the CAP score alone was found to be a useful indicator of the presence and severity of metabolic syndrome [18]. Using traditional statistical modeling, we previously validated this finding, confirming that the CAP score alone can be used to detect metabolic syndrome with moderate accuracy (area under the receiver operating characteristic curve [ROC] of 0.79), and the accuracy was improved to 0.88 when combined with other biomarkers [19].…”
Section: Introductionmentioning
confidence: 61%
“…In the current study, NAFLD was evaluated by CAP, which was a newly developed non-invasive and quantitative evaluation method and has been widely used as a first-line assessment for screening fatty liver [22]. In addition, CAP values were closely associated with metabolic syndrome (MetS) and its components including obesity, hypertriglyceridemia, hyperglycemia and hypertension [32]. FLI, as is a simple, accurate and non-invasive approach, has also shown a good capability for discriminating individuals with NAFLD from those without it in a populationbased study with 7-year follow up [33].…”
Section: Table 1 Characteristics Of Subjects By Tertiles Of Serum Ft3 Levelmentioning
confidence: 99%
“…These findings are consistent with the previous studies, which have shown that liver fat quantification measured by CAP values is closely associated with MetS and its components. 24,25 MRI-PDFF performed in adolescent girls and young women also showed that a low threshold on MRI-PDFF is predictive of MetS. 26 Abnormal LFTs have been used as a noninvasive marker of NASH.…”
Section: Discussionmentioning
confidence: 99%